2020
DOI: 10.1088/1755-1315/530/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of bacteria associated with Nudibranchs to control Vibrio spp.

Abstract: Shrimp culture process of Litopenaeus vannamei could not be separated from the disease threats. Vibriosis is the main cause of a decrease in aquaculture production. Vibrio harveyi is a pathogenic bacteria that can caused high mortality and Vibro parahaemolyticus can also cause massive financial losses in shrimp culture. The use of antibiotics to control vibriosis, however, has a negative impact. For example, it resulted in the shrimp resistance to pathogenic bacteria. The potential of bacteria that are symbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Another study from Indonesia described the anti-MRSA, cytotoxicity, and anti-HSV-1 activity of bacterial symbionts from the viscera of nudibranchs . The presence of bacterial symbionts in a nudibranch to inhibit the growth of pathogenic Vibrio species (Prayitno et al, 2020) was also revealed. In addition, the nudibranch Rostanga alisae harbors a high diversity of specific endo-and extracellular bacteria, and some of them are previously unknown as symbionts of marine invertebrates (Zhukova et al, 2022).…”
Section: Natural Products Of Mollusks' Bacterial Symbiontsmentioning
confidence: 97%
“…Another study from Indonesia described the anti-MRSA, cytotoxicity, and anti-HSV-1 activity of bacterial symbionts from the viscera of nudibranchs . The presence of bacterial symbionts in a nudibranch to inhibit the growth of pathogenic Vibrio species (Prayitno et al, 2020) was also revealed. In addition, the nudibranch Rostanga alisae harbors a high diversity of specific endo-and extracellular bacteria, and some of them are previously unknown as symbionts of marine invertebrates (Zhukova et al, 2022).…”
Section: Natural Products Of Mollusks' Bacterial Symbiontsmentioning
confidence: 97%
“…Dari isolat tersebut hanya satu isolat (SM-N-3(2)/7) yang teridentifikasi memiliki kemampuan melawan V.harveyi dan V. parahaemolyticus. Isolatnya adalah bakteri batang gram negatif, berdasarkan identifikasi molekuler menggunakan 16S rRNA itu terkait erat dengan Pseudoalteromonas piscicida strain NBRC (99%) (Sarjito, et al, 2020). Penelitian lain menunjukkan bahwa ekstrak kasar dari supernatan kultur Pseudoalteromonas rubra dan V. salarius, simbion dari nudibranch, memiliki aktivitas anti-MRSA, yang pasti disebabkan oleh senyawa yang diproduksi dan disekresikan oleh bakteri.…”
Section: Hasil Dan Pembahasanunclassified
“…We previously investigated the potential of nudibranch-associated bacteria against Vibrio harveyi and V. parahaemolyticus. Pseudoalteromonas piscicida isolated from nudibranchs had inhibitory activity of 19.4 and 10.63 mm, respectively (Sarjito et al 2020). In the marine nutrient cycle, a sponge, which lives as a filter feeder, plays a zoobenthic roles, allowing marine microbes to easily infiltrate and reside in the sponge body.…”
Section: Introductionmentioning
confidence: 99%